Contrasting styles of lead-zinc-barium mineralization in the Lower Benue Trough, Southeastern Nigeria (2017)
In the Lower Benue Trough of Southeastern Nigeria, lead-zinc-barium mineralization occurs as widely distributed epigenetic fracture-controlled vein deposits which are restricted to Albian – Turonian sediments. Detailed field studies carried out in Ishiagu, Enyigba-Ameki-Ameri, Wanikande-Wanakom, and Gabu-Oshina which together constitute the four main areas of mineralization in the Lower Benue Trough, show that mineralization appears restricted to NW-SE and N-S fractures while the more common NE-SW fractures are barren. Apart from the Enyigba area, igneous bodies are found in the vicinity of the ore deposits while in the Wanikande area, barite veins and veinlets were observed to be closely interwoven with intrusive bodies. The host lithologies are highly varied, ranging from shales to siltstones, sandstones and occasionally igneous bodies. The ore assemblage also varies remarkably, with lead:zinc:barium ratios ranging from approximately 3:1:0 at Ishiagu, to 2:1:0 at Enyigba, 1:0:2 at Wanikande and nearly 100% barite at Gabu-Oshina. Thus, there is a remarkable increase in barite content from the southwest (Ishiagu) to the northeast (Gabu). The characteristics of the ore deposits roughly fit the base metal type mineralization known as clastic dominated lead-zinc-barium deposits. This study forms part of a mineral potential database which is invaluable for any detailed exploration venture in the area.